Embedded gate CVD MoS2 microwave FETs - Atresh Sanne (Nature Portfolio, 2017)
High-frequency electronics: embedded gates boost MoS2 radio frequency transistors 2D materials enable radio frequency transistors, yet the absence of a bandgap in graphene limits its maximum oscillation frequency. A team lead by Sanjay Kumar Banerjee at the University of Texas at Austin fabricated radio frequency field-effect transistors using monolayer MoS2 grown by chemical vapor deposition. The devices feature an embedded gate structure which ensures optimal gate control over the conducting channel and improves the channel-dielectric interface, whilst requiring a reduced number of fabrication steps. As a result, the device exhibits a maximum oscillation frequency as high as 11.4 GHz, an I ON/I OFF current ratio of 108, and a remarkable transconductance of 70 μS/μm, among the highest achieved so far for MoS2 devices fabricated by means of chemical vapor deposition. These results advance the state-of-the-art performance of atomically thin radio frequency transistors.